Marriage Dispensation and Family Resilience: A Case Study of the Bener Meriah Shariah Court, Aceh Province - Darmawan Darmawan; Asmaul Husna; Mirza Rahmatillah; Helmi Imran (Universitas Islam Negeri Jakarta, 2022)
The regulation on marriage dispensation has encouraged the increase in early marriage in various regions in Indonesia, including in Bener Meriah, Aceh. Early marriage has a negative impact on family resilience as it raises problems leading to divorce. This is a normative legal study with a case study approach. Data collection was carried out employing a document study, namely Sharia Court Decisions and related literature. This study concludes a significant relationship between marriage dispensation, high underage marriages, and weak family resilience. In granting marriage dispensation, the Sharia Court judges consider legal and extra-legal grounds. The dispensation stipulation has met the legal requirement, although the legal reasonings are unconvincing. Furthermore, early marriage has an impact on increasing divorce rates due to issues such as psychological problems and reproductive readiness, as well as adverse effects caused by divorce. Therefore, concrete and strategic steps are needed with the involvement of various groups, including the government, ulama, and traditional leaders, who are able to promote family resilience in society.Keywords: marriage dispensation; underage marriage; family resilience; sharia court AbstrakKebijakan dispensasi nikah telah mendorong peningkatan pernikahan dini di berbagai daerah di Indonesia, termasuk di Bener Meriah, Aceh. Pernikahan dini berdampak negatif terhadap ketahanan keluarga karena menimbulkan masalah yang berujung pada perceraian. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan studi kasus. Pengumpulan data dilakukan dengan studi dokumen yaitu Putusan Mahkamah Syar’iyah dan literatur terkait. Penelitian ini menyimpulkan bahwa terdapat hubungan yang signifikan antara dispensasi perkawinan, tingginya angka perkawinan di bawah umur dan lemahnya ketahanan keluarga. Dalam pemberian dispensasi nikah, hakim Mahkamah Syar’iyah mempertimbangkan alasan hukum dan alasan di luar hukum. Ketentuan dispensasi tersebut telah memenuhi syarat hukum, meskipun pertimbangan hukumnya tampak memaksakan. Lebih lanjut, pernikahan dini berdampak pada meningkatnya angka perceraian karena masalah-masalah seperti masalah psikologis dan kesiapan reproduksi, serta dampak buruk akibat perceraian. Oleh karena itu, diperlukan langkah- langkah konkrit dan strategis dengan melibatkan berbagai pihak, termasuk pemerintah, ulama, dan tokoh adat, yang mampu mendorong ketahanan keluarga dalam masyarakat.Kata Kunci: dispensasi pernikahan; pernikahan dini; ketahanan keluarga; Mahkamah Syar’iyah